2017
DOI: 10.1007/jhep10(2017)067
|View full text |Cite
|
Sign up to set email alerts
|

Two loop QCD corrections for the process pseudo-scalar Higgs → 3 partons

Abstract: We present virtual contributions up to two loop level in perturbative Quantum Chromodynamic (QCD) to the decay of pseudo-scalar Higgs boson (A) to three gluons (g) and also to quark (q), anti-quark (q) and a gluon. With appropriate crossing, they are well suited for predicting the differential distribution of A in association with a jet in hadron colliders up to next-to-next-to-leading order (NNLO) in strong coupling constant and also for the subsequent decay of A to hadrons. We use effective field theory appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 101 publications
(129 reference statements)
4
18
0
Order By: Relevance
“…The breaking of parity symmetry in the non-planar content explains the origination of R NP . We also would like to stress that the discrepancy between planar and non-planar contributions is still consistent with the maximal transcendentality principle first introduced in study of anomalous dimensions in [112,113] and later observed for the remainder functions of various form factors [11,14,[36][37][38][39][40][41][114][115][116][117][118][119]. Therefore, we expect that the new non-planar contribution will also be a universal function that appears in generic (non-planar) gauge theories.…”
Section: Jhep04(2021)176supporting
confidence: 80%
“…The breaking of parity symmetry in the non-planar content explains the origination of R NP . We also would like to stress that the discrepancy between planar and non-planar contributions is still consistent with the maximal transcendentality principle first introduced in study of anomalous dimensions in [112,113] and later observed for the remainder functions of various form factors [11,14,[36][37][38][39][40][41][114][115][116][117][118][119]. Therefore, we expect that the new non-planar contribution will also be a universal function that appears in generic (non-planar) gauge theories.…”
Section: Jhep04(2021)176supporting
confidence: 80%
“…We obtain the analytic expressions, and find that maximal transcendental part is universal, namely, independent of the operators. This provides further support of the maximal transcendentality principle introduced in study of anomalous dimensions in [41,42] and then observed for the form factor of tr(F 2 ) in [43] and later also for other operators [12,13,31,[44][45][46][47][48][49][50][51][52]. Besides, the lower transcendentality degree-3 and degree-2 parts also contain universal building blocks, which was also observed in the previous results with dimension-six operators [13].…”
Section: Introductionsupporting
confidence: 87%
“…This has been known for the kinematic independent quantities such as anomalous dimensions [38,39]. For pseudo-scalar Higgs amplitudes involving qqg states, the universal maximally transcendental part was also noted in [89].…”
Section: Discussionmentioning
confidence: 81%